Development and Validation of a Person-Centered Care Assessment Questionnaire for Daycare Centers for Older Adults. (9th August 2021) - Chin, Young Ran; Lee, Hyo Young; Lee, Mi-Joung
Daycare services serve to prolong aging at home. This decreases both families' care burden and the government's financial burden. We identified key factors in the person-centered approach of South Korean daycare center workers to develop and validate a Korean person-centered care questionnaire. Twenty-one items were developed, and 10 expert interviews were conducted. The items were applied to 271 daycare center staff (19.2% male vs. 80.0% female, mean age = 50.68 ± 11.37 years) to evaluate their reliability and validity. Twenty items concerning intimate relationships and the environment, consumers' self-determination, and home-likeness domains were derived, explaining 40.28%, 10.44%, and 6.97% of the total variance, respectively. The overall tool's Cronbach's alpha was 0.905, demonstrating internal consistency. Inter-rater agreement ranged from 0.221 (fair) to 0.765 (good). This tool will be useful for individual staff members as well as for the National Health Insurance Service's evaluations of service quality at daycare centers.